Analysis of Rice Production Trends and Forecasting Using the Least Square Method in West Sumatra Province - Andreas Sitanggang (Journal of Innovation, Business Management and Entrepreneurship, 2025)
Rice is a strategic commodity that is the main food for most people in Indonesia. West Sumatra Province as one of the regions in Indonesia where most of the people consume rice is faced with fluctuations in rice production. Information on production trends and forecasts of future rice production is very important in efforts to maintain the availability of rice for the community. This study aims to identify rice production trends and predict rice production in West Sumatra Province. The data used in this study are secondary data obtained from the Central Statistics Agency, namely time series data on rice production in West Sumatra Province in 2018-2024. The data analysis used to identify rice production trends in West Sumatra Province is descriptive analysis and to predict rice production in West Sumatra, the Least Square method and Mean Absolute Percentage Error (MAPE) analysis are used to measure the level of accuracy of the forecast data. The results of the study show that throughout 2018-2024, rice production in West Sumatra Province showed a negative trend with an average decrease in production of 11,480.95 tons per year and it is predicted that in 2025-2029 rice production in West Sumatra Province will experience a decrease in production with an average decrease of 7,222.75 tons per year.